INFANTICIDE DENGAN TINDAKAN MUTILASI: TINJAUAN FORENSIK BERDASARKAN PEMERIKSAAN LUAR DAN DALAM JENAZAH BAYI - Rosmawaty, Rosmawaty; Yosse Rizal; Khomeini, Khomeini (Nusantara Hasana Journal, 2025)
Infanticide accompanied by mutilation represents an extreme form of fatal violence against neonates and poses significant challenges in forensic andmedicolegal investigations. In criminal proceedings, the absence of witnesses and limited non-medical evidence often complicate the determination of the cause and mechanism of death, particularly when mutilation involving sharp force trauma is present. Forensic medicine, through comprehensive postmortem examination and the preparation of visum et repertum, plays a crucial role in providing objective and scientifically valid evidence. This article aims to analyze the mechanism of death in a case of infanticide with mutilation based on external and internal examinations of a neonatal body. This study employed a forensic case report design using data derived from a visum et repertum Pro Justitia. External examination revealed dismemberment of body parts, multiple abrasions, lacerations, and irregular open wounds consistent with sharp force trauma associated with mutilation. Internal examination demonstrated hemorrhagic infiltration of the cranial bones and dilated cerebral blood vessels, indicating vital reactions due to blunt force trauma. These findings indicate that the cause of death was blunt force head trauma sustained while the victim was alive, whereas the mutilation caused by sharp force trauma occurred during the peri-mortem or post-mortem period. It is concluded that visum et repertum provides strong evidentiary value and plays a central role in determining the mechanism of death and supporting legal proceedings in cases of infanticide with mutilation.